The Influence of Wind Direction during Storms on Sea Temperature in the Coastal Water of Muping, China - Xiangyang Zheng; Yana Ding; Yandong Xu; Tao Zou; Chunlei Wang; Qianguo Xing (Journal of Marine Science and Engineering, 2021)
Sea temperature structures are important for water stratification and marine ecosystems. In the coastal water of Muping, China, stationary measurements of sea temperature captured temporal temperature changes during two summer storm events. The north component of the wind during the two storms was opposite. The temperature responded differently to wind directions in the two storm events. A well-validated numerical ocean model was used to investigate the mechanism of sea temperature variation of the coast of Muping. The model revealed that the southerly and easterly wind was upwelling-favorable in the study area. They generated the shoreward transport of bottom cold water, which induced bottom water cooling, enhanced stratification, and weakened vertical mixing. On the other hand, the northerly and westerly wind was downwelling-favorable and enhanced turbulent mixing. The alongshore upwelling-favorable wind caused more cross-shore transport than cross-shore upwelling-favorable wind, which resulted in stronger bottom cooling. Similarly, alongshore downwelling-favorable wind generated lower temperature than cross-shore wind. A surface cold-water band was formed in the second storm. Although it was formed during upwelling-favorable wind, the temperature balance analysis indicated that vertical mixing and westward horizontal advection were the two dominant processes compared to upwelling.